Operational analysis of the innovative sewage manhole for gravity sewage networks - Kowalski, Dariusz; Iwanek, Małgorzata; Kowalska, Beata; Suchorab, Paweł; Kwietniewski, Marian; Duklewski, Wiesław (Instal, 2020)
The reliable operation of sewage networks is one of the key elements necessary for the existence and development of urban areas. The assurance of alternative paths of sewerage conveyance by proper network shaping is one of the ways of increasing network’s reliability. It can be achieved by transforming branched networks into loops. However, to connect channels into looped structures, it is required to intersect channels safely. The aim of this paper is to present a new, innovative sewage manholes, which can be used in both a sanitary and storm gravity sewage network. The additional aim is to present the results of a hydraulic test of a manhole prototype. The innovative manhole is characterized by a specific manhole base construction. It enables a safe, two-level channel intersection during normal operation. In case of a channel failure (blocked outflow), the sewage flow is redirect into the other channel. The manhole constructor is patented (Patent no PL 229311).